The Stabilizing Role of Net Foreign Asset Returns - Adler, Gustavo; Garcia-Macia, Daniel (Washington, D.C. : International Monetary Fund, 2018)
With the rapid growth of countries' foreign asset and liability positions over the last two decades, financial returns on those positions ('NFA returns') have become material drivers of current accounts and net stock positions. This paper documents the relative importance of NFA return versus trade channels in driving NFA dynamics, for a sample of 52 economies over 1990-2015. While persistent trade imbalances have been a strong force leading to diverging NFA positions, NFA returns have played an important stabilizing role, mitigating NFA divergence. The stabilizing role of NFA returns primarily reflects the response of asset prices, rather than yield differentials or exchange rates. There is also evidence of heterogeneity in the speed of NFA adjustment, with emerging market economies adjusting more rapidly than advanced economies, and reserve-currency countries adjusting more slowly than others. The paper also documents the role of NFA returns as insurance against domestic and global income shocks, with a focus on reserve-currency countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet